INTEGRATING VIBRATION SENSING AND NON-SPEECH VISUALIZATION TO NOTIFY HEARING IMPAIRED STUDENTS REGARDING FIRE - ABDUL MANAF, MARLINA (2015)
This research aims to develop a fire notification system conceptual model for hearing impaired students to better notify them on the occasion of fire. The current fire alert measures are particularly less effective when alerting the hearing impaired people especially on fire. Findings from the literature study indicated that this was due to a matter that modality have been dealt separately. It might be because designers neglect the main HCI concepts and do not serve products based on the demands and requirements of the impairments. They are mostly driven by market trends and macroeconomics forces. Supposing, designs must rely on multimodal interaction for optimum information access; besides considering on the universal design and user support concepts.